2016
DOI: 10.1002/nau.23011
|View full text |Cite
|
Sign up to set email alerts
|

Urinary neurotrophic peptides in postmenopausal women with and without overactive bladder

Abstract: Our data does not support a relationship between urinary neurotrophin levels and OAB in age-matched postmenopausal women. Further research is necessary to elucidate the role of urinary neurotrophins in the diagnosis and management of OAB. Neurourol. Urodynam. 36:740-744, 2017. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 24 publications
(47 reference statements)
1
13
0
2
Order By: Relevance
“…It is thought that NGF, which is overexpressed in pathological bladder, has a knock on effect to sensitise afferent C‐fibres, leading to sensory urgency, and ultimately reflex bladder hyperactivity, causing urinary frequency and urgency UI. However, in a recent published cross‐sectional study, no significant difference was found between OAB and healthy control subjects after controlling the confounding factors as much as possible in postmenopausal women …”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…It is thought that NGF, which is overexpressed in pathological bladder, has a knock on effect to sensitise afferent C‐fibres, leading to sensory urgency, and ultimately reflex bladder hyperactivity, causing urinary frequency and urgency UI. However, in a recent published cross‐sectional study, no significant difference was found between OAB and healthy control subjects after controlling the confounding factors as much as possible in postmenopausal women …”
Section: Discussionmentioning
confidence: 90%
“…. There were 17 published studies eventually included in our meta‐analysis. The 17 studies (1 cross‐sectional study and 16 case‐control studies) included 1678 subjects in total (1137 patients, 541 controls).…”
Section: Resultsmentioning
confidence: 99%
“…To date, several potential OAB biomarkers have been identified in both pre-clinical and clinical studies, including CGRP, ERK1/2, OTC3, VAChT, BDNF, and NGF [22,72,[94][95][96][97][98]. In this regard, the authors aimed to establish whether the administration of O-1602 is able to eradicate RA-induced disturbances in the levels of OAB markers in the bladder urothelium, detrusor muscle, and/or urine in female rats.…”
Section: Biochemical Studiesmentioning
confidence: 99%
“…Interestingly, Pennycuff et al could not find differences in urinary NGF levels between OAB and controls, but this was not discussed in detail by Sheng et al Furthermore, two publications using alternative NGF‐ELISAs (from Meso Scale Discovery (Rockville, MD) or PeproTech Inc (Rocky Hill, NJ)) also reported no differences in urinary NGF levels for cases (bladder pain syndrome/interstitial cystitis, OAB, or neurogenic lower urinary tract dysfunction) and controls. In fact, NGF concentrations were below detection level (10 pg/mL), indicating that current ELISA technology was not sensitive enough to detect NGF in urine.…”
mentioning
confidence: 97%
“…The Promega assay did not detect NGF, but other urinary components, such as immunoglobulin G, and in 2014, it was withdrawn from the market. The remaining four studies used NGF‐ELISAs from Wuhan Boster Biological Technology, Ltd. (Wuhan, China), from RayBiotech (Norcross, GA), and from a not‐specified provider …”
mentioning
confidence: 99%